Detection of Negative Pickup Ions at Saturn's Moon Dione. Issue 7 (2nd April 2020) - Nordheim, T. A.; Wellbrock, A.; Jones, G. H.; Desai, R. T.; Coates, A. J.; Teolis, B. D.; Jasinski, J. M.
Abstract: We investigate a possible negative ion feature observed by the Cassini Plasma Spectrometer (CAPS) during a flyby of Saturn's moon Dione that occurred on 7 April 2010. By examining possible particle trajectories, we find that the observed particles are consistent with negative pickup ions originating near the moon's surface. We find that the mass of the negative pickup ions is in the range of 15–25 u and tentatively identify this species as O −, likely resulting from ionization and subsequent pickup from Dione's O2 ‐CO2 exosphere. Our estimates show that the negative ion density is ~3 × 10 −3  cm −3 . This is comparable to, but slightly smaller than, that previously reported for the density of O2 + pickup ions for the same flyby, indicating that negative pickup ions may represent a major loss channel for Dione's exosphere. Key Points: Analysis of data from the Cassini Plasma Spectrometer confirms negative pickup ions originating from Saturn's moon Dione The negative pickup ions are consistent with O − originating from Dione's exosphere Density estimates indicate that negative pickup ions may represent a significant loss channel for Dione's exosphere